Application of the standard coupled-mode formalism to the analysis of holey photonic crystals. Issue 6 (30th March 2019) - Giladi, Lidor; Smith, Elena; Shteeman, Vladislav; Hardy, Amos A.
ABSTRACT: Presented below is a new, Standard Coupled-mode Theory (CMT) based approach for analysis of optical characteristics of holey photonic crystals (i.e., photonic devices, built on periodicity of holes in dielectric media). This class of devices encompasses the majority of photonic crystal fibres and several kinds of modern thresholdless lasers. Naturally, holey photonic crystals were considered as a sequence of holes, surrounded by dielectric media. This model made it impossible to utilise CMT for analysing their characteristics. The underlying idea of our approach is a different physical model, considering holey photonic devices as a sequence of coupled dielectric spots (waveguides), surrounded by air. This model can be combined with the Standard Coupled-mode formalism. The latter combination allows fast (on a timescale of several minutes to tens of minutes) and accurate analysis of holey photonic devices. Moreover, it gives a deeper insight into the behaviour of EM fields in holey photonic crystals.